The interactive effects of Easyzyme and phytase in diets containing high-fiber co-products on growth performance of nursery pigs - A B Graham; S Nitikanchana; Jong J.A. De; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
Two experiments were conducted to determine the effects of a dietary non-starch polysaccharide enzyme (Easyzyme, Archer Daniels Midland Co., Decatur, IL) or phytase (Phyzyme, Danisco Animal Nutrition, St. Louis, MO) addition in corn-soybean meal or high-fiber diets on nursery pig growth performance. In Exp. 1, 192 nursery pigs (PIC 327 × 1050, initially 21.8 lb) were allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial. Main effects were diet type (corn-soybean meal or corn-soybean meal plus 30% wheat middlings) with or without added dietary enzyme (Easyzyme Mixer 1, 1 lb/ton). Each experiment involved 6 pigs per pen and 8 replications per treatment. All diets contained 340.5 phytase units (FTU)/lb. From d 0 to 21, pigs fed corn-soybean meal diets had greater (P<0.001) ADG than those fed diets containing 30% wheat midds. Added Easyzyme had no effect on ADG. ADFI and F/G exhibited a diet type × Easyzyme interaction (P<0.03). In corn-soybean meal diets, Easyzyme had no effect on ADFI or F/G, whereas in diets containing 30% wheat midds, Easyzyme increased ADFI and worsened F/G.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; By-products; Enzyme; Fiber; Phytase; Nursery pig